Teaching english through traditional ecuadorian legends to develop the reanding and listening skilis - Criollo Flores, Mónica Andrea; Sarango Solano, Erika Natalia
This monographic work provides people, especially teachers, with information, material, and activities to teach English and develop the reading and listening skills through the use of Ecuadorian legends. The work explains and points out the importance of culture during the teaching and learning of a second language. Legends are part of our culture and they become key resources to catch students´ attention and get them involved during the reading and listening processes. Besides, the main objective of this work, therefore, is to offer material, in the form of legends, for improving the reading and listening skills. If anything is proven in this monographic research, it is only that there exists interest in the type of methodology and material that is being presented here. Another objective of using legends to teach English is to make students spend their time doing worthy things and to feed their minds with valuable readings. The reward for anyone who carries out this type of work is indescribable because it makes possible the application of our history and culture while teaching English, the universal language.